Pilar keberhasilan: Pentingnya bahasa Arab dan Inggris untuk mahasiswa di dunia bisnis - Ba’Abdullah, Adam (Maliki Interdisciplinary Journal, 2024)
The Foreign languages or more precisely international languages have a central role in the world of entrepreneurship and global business. Mastery of international languages is used as the main weapon in understanding global market flows. Its main function is as a communication tool for mutual understanding between parties involved in the business. Thus creating ease of transactions in international business. Two languages that are influential and have quite an important role in the international world are Arabic and English. In the Middle East, which is full of business, economic and resource-rich opportunities, Arabic has a major role as a means of communication. More than 420 million people worldwide speak Arabic and it has particular relevance to businesses in Middle Eastern countries. Therefore, Arabic can be said to be very important. Meanwhile, English is the most popular and widely used official international language. This language is used by 1.452 billion speakers from 67 countries, where those countries recognize English as their official language. Among these countries are the United Kingdom, the United States, New Zealand and Australia. English is also a language whose use is almost widespread in all fields, a clear example of which is its use in universities in countries around the world. Its use is almost uniform in any major. In the world of entrepreneurship, English is increasingly needed, especially in the economic and business markets which are transforming into the main weapon in managing trade strategies. Thus making English increasingly popular as a means of interaction on the world stage. For students, Arabic and English language skills are needed as an added value when working in international business.